Uwagi nad problemami inkulturacji Kodeksu Napoleona w Królestwie Polskim — wątpliwości na tle art. 530 - Wiśniewska, Dorota (Wydawnictwo Uniwersytetu Wrocławskiego, 2019)
A serious problem can arise when a society has to deal with regulations not adapted to its internal relations, regulations that have been imposed on that society. Such a situation occurred in Poland in the early nineteenth century in connection with the introduction of the Napoleonic Code within the territory of the Duchy of Warsaw. This generated a lot of controversy, not only among members of the Council of State, but also among wealthy and lesser nobility as well as Catholic clergy. The state was characterised by numerous remnants of feudalism. The conditions, when it came to both social and economic relations, were different than those in France. Consequently, the provisions of the Code referring to property were not fully applicable in practice.After the fall of the Duchy of Warsaw the Napoleonic Code remained in force in the Kingdom of Poland and the Free City of Kraków. However, it still had many opponents in the Kingdom of Poland. In the end there emerged a concept of reform of property law, with one of its points being a change in the provisions guaranteeing inferior owners a possibility of redeeming their obligations. Such a right was guaranteed by Article 530 of the Code, which could lead to dominium utile or inferior ownership being transformed into dominium plenum or full ownership. A draft amendment was prepared by the Legislative Deputation and then adopted by the parliament on 13 June 1825.The inculturation of the Code in the Kingdom of Poland, a country on a lower level of socio-economic development than France, was doomed to failure. While in the Duchy of Warsaw the Napoleonic Code was fictitiously used in practice, as it were, in the Kingdom of Poland legislative work was undertaken to change civil law and adapt it to the conditions in the country.
Keywords: Kodeks Napoleona; Księstwo Warszawskie; Królestwo Polskie; podwójna domena; dzierżawa wieczysta; renta wieczysta; inkulturacja kodeksu napoleońskiego